Improving Students’ Reading Ability of Report Text by Using Collaborative Strategic Reading (CSR) Method at Grade X SMA Negeri 1 Batang Toru - Tina Erwinda; Rahmat Huda; Anggina Syahrina Daulay; Hestika Wildani; Naimah; Nurhidayah (CV. Alfa Pustaka, 2025)
This research intends to: 1) Analyze the improvement of students' reading ability related to report text following the introduction of the Collaborative Strategic Reading (CSR) technique in grade X SMA Negeri 1 Batang Toru. 2) Identify the variations in reading skills between students utilizing the CSR method compared to conventional methods. 3) Assess students' answers to the deployment of the CSR approach in the reading comprehension process. This study applies Classroom Action Research (CAR) methodology with 36 kids as subjects, of whom 33 participated. Data-gathering approaches were accomplished using tests, questionnaires, and observations. The data reveal that the average score of students in the pre-test was 63.75, or 41.66%, whereas the post-test average jumped to 71.25, or 70.25%. The percentage of pupils achieving the Minimum Completeness Criteria (KKM) in the pre-test was 22.22%, increasing to 70.25% in the post-test. Students' answers to the CSR technique were also positive, with 75% expressing favorable feedback. The findings reveal that the application of the Collaborative Strategic Reading (CSR) approach is helpful in boosting students' reading abilities regarding report materials at SMA Negeri 1 Batang Toru.